Analysis of the HeartWare HVAD pump characteristics under pulsatile operation. (July 2021) - Mapley, Martin C.; Seah, E-Peng; Semenzin, Clayton; Wu, Eric; Pauls, Jo P.
Highlights: Accuracy of the flow estimator was dependent on flow rate. Speed modulation led to high instantaneous power consumption. Quantised sine speed modulation reduced the magnitude of overshoot. Abstract: Rotary blood pumps (RBPs) are clinically utilised to support patients suffering from later stage heart failure and although the development of these devices has led to vast improvements, they still lack a physiological pulse. To overcome the drawbacks of the absence of pulsatility in RBPs, physiological control systems have been developed which introduce pulsatility by rapid speed modulation. Much of the research introducing pulsatility in patients supported by a HeartWare HVAD has focussed on haemodynamic output with no investigations on the limitations of the pump's electrical characteristics. Accordingly, the aim of the present study was to investigate the effect of rapid speed modulation on the accuracy of the flow estimator and power consumption as well as analysis of the shape of the flow and pressure waveforms when speed modulation was performed with quantised sine and square waves. The accuracy of the flow estimator was shown to be dependent on flow rate and independent of fluid viscosity, base speed or pulse amplitude. The average power consumption was shown not to differ greatly when pulsatility was introduced increasing by 0.72 ± 0.31 W per 1000 RPM of peak-to-peak speed modulation. However, the instantaneous power draw was shown to increase by up to three times, particularly at low base speeds. Speed modulation using a quantised sine wave qualitatively demonstrated reductions in overshoot from the target speed when compared to speed modulation using a square wave. Information contained in this article will assist researchers in the development of physiological control systems employing rapid speed modulation techniques.